Height‐dependent transition from 3‐D to 2‐D turbulence in the hurricane boundary layer. Issue 7 (12th April 2013) - Byrne, David; Zhang, Jun A.
Abstract [1] Here we show, from in situ aircraft measurements in the hurricane boundary layer, a height‐dependent transition of the flow from 3‐D to 2‐D turbulence. This marks a fundamental change in the energy dynamics of the hurricane boundary layer due to the fact that in 3‐D, energy flows downscale from larger to smaller scales, whereas in 2‐D, it flows upscale, from smaller to larger scales. These results represent the first measurement of the 2‐D upscale energy flux in the atmosphere and also the first to characterize the transition from 3‐D to 2‐D. It is shown that the large‐scale parent vortex may gain energy directly from small scales in tropical cyclones.